School Management in the Implementation of Inclusive Education at SMP Negeri 7 Pemalang (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
This study analyzes the implementation of inclusive education management at SMP Negeri 7 Pemalang through the managerial functions of planning, organizing, implementation, and supervision, while examining pedagogical capacity strengthening that supports inclusive learning practices. The research employed a qualitative case study approach involving 12 informants, including the principal, vice principal for curriculum, special education teachers, subject teachers, homeroom teachers, and students with special needs. Data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed descriptively through data reduction, data display, and conclusion verification using source and technique triangulation. The findings demonstrate that inclusive education management has been systematically implemented through the integration of inclusive policies into school planning, preparation of Individualized Education Programs (IEPs), collaborative learning practices in regular classrooms, and periodic supervision by school leaders. The study also reveals significant strengthening of teachers’ pedagogical capacity, particularly in differentiated instruction, adaptive classroom management, flexible assessment development, digital learning media utilization, and collaborative student-centered learning strategies. Nevertheless, implementation remains constrained by the limited availability of special education teachers, uneven teacher competence in inclusive pedagogy, insufficient assistive learning facilities, and evaluation systems that are not yet fully oriented toward continuous quality improvement. The study’s novelty lies in integrating inclusive management functions with measurable indicators of pedagogical capacity development to support sustainable and effective inclusive education practices.